Propuesta para la reducción de residuos sólidos no reciclables en cadenas de restaurantes de comidas rápidas (2020)
The following work describes the current situation in the world, focusing mainly on Colombia, with the problem of packaging, defining the importance that these have for fast food chains and the great environmental problems they have generated throughout their history. At the same time, figures and data of the production, of the pollution and impacts they generate and of the entire market that move the packaging are collected, in the same way, information is gathered on the initiatives that have been carried out by the fast food chains in search of the reduction of the impact that the packaging caused. Finally, according to all the collected bibliography, look for different viable and feasible solutions to reduce the use of packaging in the restaurants of fast food chains and using the Super Decisions software the best alternative for this problem was determined.